Knowledge, attitude, and practice of embryo transfer among women who underwent in vitro fertilization-embryo transfer - Xu, Yangying; Hao, Cuifang; Zhang, Huimin; Liu, Yingxue; Xue, Wei (Frontiers in Cell and Developmental Biology, 2024)
Background and Objective: The infertile patient’s knowledge, attitude, and practice (KAP) toward embryo transfer may affect treatment outcomes and the mental health of women who underwent in vitro fertilization-embryo transfer (IVF-ET). This study aimed to investigate the KAP of embryo transfer among women who underwent IVF-ET. Methods: This cross-sectional study was conducted on women who underwent IVF-ET at our Hospital between May 2023 and November 2023, using a self-designed questionnaire. Results: A total of 614 valid questionnaires were finally included. The mean KAP scores were 19.46±5.06 (possible range: 0-28), 39.41±5.20 (possible range: 12-60), and 48.02±6.75 (possible range: 0-60), respectively. The structural equation model demonstrated that knowledge has a direct effect on attitude (β=0.27, P<0.001) and attitude has a direct effect on practice (β=0.55, P<0.001) and anxiety (β=0.59, P<0.001). Moreover, multivariable linear regression analysis showed that anxiety score (coefficient = 0.09, 95% confidence interval (CI): 0.03-0.16, P = 0.003), BMI (coefficient = 0.09, 95%CI: 0.03-0.16, P = 0.003), education (coefficient= 5.65-6.17, 95%CI: 1.09-10.7, P<0.05), monthly per capita income (coefficient = 1.20-1.96, 95% CI: 0.21-3.07, P = 0.05), reasons for IVF (coefficient = -1.33--1.19, 95% CI: -2.49-0.09, P<0.05), and more than five years of infertility (coefficient = -1.12, 95% CI: -2.11--0.13, P = 0.026) were independently associated with sufficient knowledge. Knowledge (coefficient = 0.19, 95% CI: 0.12-0.26, P < 0.001), anxiety (coefficient = 0.39, 95% CI: 0.34-0.45, P < 0.001), monthly per capita household income >10000 (coefficient = 1.52, 95% CI: 0.61-2.43, P < 0.001), and 3 or more cycles of embryo transfer (coefficient = -2.69, 95% CI: -3.94--1.43, P < 0.001) were independently associated with active attitude. Furthermore, attitude (coefficient = 0.21, 95% CI: 0.11-0.30, P<0.001) and anxiety (coefficient = 0.57, 95% CI: 0.49-0.65, P < 0.001) were independently associated with proactive practice. Conclusion: Women who underwent IVF-ET had inadequate knowledge and negative attitudes but proactive practice toward embryo transfer, which were affected by anxiety, income, and reasons for IVF. It is necessary to strengthen the continuous improvement of patient education to improve the management of embryo transfer.